Deciphering Water Oxidation Catalysts: The Dominant Role of Surface Chemistry over Reconstruction Degree in Activity Promotion - Li An; Jianyi Li; Yuanmiao Sun; Jiamin Zhu; Justin Zhu Yeow Seow; Hong Zhang; Nan Zhang; Pinxian Xi; Zhichuan J. Xu; Chun-Hua Yan (Nano-Micro Letters)
Highlights Demonstrate that the key factor to determine the activity of reconstructed surfaces is the surface chemistry, instead of reconstruction degree using the popular perovskite LaNi1-xFexO3 oxides as model materials. Fe content can influence both the surface reconstruction degree, the activation degree, and the activity of reconstructed surfaces. The oxygen evolution reaction activity of reconstructed catalysts is primarily governed by the chemistry of the reconstructed surface species.